Islam and Maritime Security Cooperation Zone for Combating Terrorism: An Overview of Islamic Legal Thought - Prakasa, Satria Unggul Wicaksana; Al-Fatih, Sholahuddin; Bachtiar, Hasnan (Fakultas Syariah UINSI Samarinda, 2023)
This article aims to examine the phenomenon of cooperation among Southeast Asian countries in dealing with the case of maritime security and counter-terrorism. The study uses the legal approach covering both international law and Islamic law perspectives. The finding of this article reveals that the implementation of the ASEAN Convention on Counter-Terrorism (ACCT) plays a crucial role in combating terrorism in the context of maritime security. Furthermore, relevant ASEAN member state authorities need follow-up support to enhance cooperation. The supports are important to counter, prevent, and suppress terrorism, terrorist organizations, associations, and networks' plans of the act. Yet, the implementation of ASEAN cooperation has faced the challenging reality of the paradox of maritime sovereignty among states in the region. The problem is likely encouraged by the factor of the internal political dynamics within each state involving the instrumentalization of the issue of national security. Instead of remaining as the problem on the surface, the conceptual initiation of the cooperation forged by religious doctrine such as ta'awun may be considered.